On k-Gamma and k-Beta Distributions and Moment Generating Functions - Gauhar Rahman; Shahid Mubeen; Abdur Rehman; Mammona Naz (Journal of Probability and Statistics)
The main objective of the present paper is to define k-gamma and k-beta distributions and moments generating function for the said distributions in terms of a new parameter k>0. Also, the authors prove some properties of these newly defined distributions.